A dual approach to third molar complexity: correlating fractal analysis with the pederson difficulty index - non-clinical research article - Cakan, Kuebra Nur; Ipek, Irem (Bmc, 2025)
BackgroundThis study aimed to evaluate the correlation between the Pederson Difficulty Index and fractal dimension analysis in impacted mandibular third molars, assessing whether fractal dimension analysis can serve as an adjunctive tool for predicting surgical difficulty.MethodsA total of 171 impacted mandibular third molars were retrospectively analyzed using digital panoramic radiographs. The Pederson Difficulty Index classified surgical difficulty based on angulation, impaction depth, and ramus relationship. Fractal dimension analysis was performed on three regions of interest: mesial, distal, and apical. Pearson correlation and one-way ANOVA assessed relationships between fractal dimension values and surgical difficulty categories.ResultsNo statistically significant correlation was found between fractal dimension values and gender across all regions of interest (p > 0.05). However, fractal dimension values demonstrated a non-significant increasing trend in distal and apical regions with increasing surgical difficulty, while mesial fractal dimension values decreased. These findings suggest potential trabecular bone adaptations related to third molar impaction, though further validation with three-dimensional imaging is required.ConclusionFD analysis offers a non-invasive and quantitative means of evaluating trabecular bone microarchitecture, which may assist clinicians in identifying areas of low or high bone resistance prior to surgical intervention. These insights can inform key surgical decisions such as flap design, osteotomy direction, and the selection of instruments (e.g., rotary tools vs. piezosurgery) to reduce trauma. Although FD should not replace established indices like the Pederson Index, it may complement them by adding microstructural depth to morphological assessments. Future integration with three-dimensional imaging and prospective clinical validation is essential to establish FD as a routine element in surgical planning.
Keywords: Fractal analysis; Pederson Difficulty Index; Impacted mandibular third molars; Surgical difficulty; Trabecular bone structure